International Perspectives on Teaching with Disability : Overcoming Obstacles and Enriching Lives - Jeffress, Michael S. (London : Routledge, 2018)
"Efforts to reduce discrimination and increase diversity on campuses, coupled with shrinking budgets causing administrators to devote more resources toward recruiting and retaining students with disabilities, are fuelling an explosion of research in the area of inclusive education. An important focus that has been largely neglected is the place of teachers with disabilities in academe. International Perspectives on Teaching with Disability brings together 25 multi-disciplinary scholars with disabilities from Africa, Canada, the Caribbean, the UK, Israel and the United States to share their struggles and successes in teaching with disability.The 18 chapters are written largely from autoethnographic perspectives grounded in solid academic research but full of anecdotes and self-reflexive narratives that provide insights into the lived experiences of the authors. Woven into the narratives are discussions of the complexities of self-disclosure and self-advocacy; the varied--and often problematic--ways disability is experienced, perceived and discussed in society and in the classroom; the challenges of navigating academe with disability, the value of disability pedagogy, the positive student outcomes achieved by teaching through disability, as well as practical applications and lessons learned that will benefit educators, administrators and students preparing to become teachers. This book is written to champion the integral place and role of disabled educators in academe. Current educators with disability will be affirmed. Those with disability aspiring to become teachers will be encouraged. Temporarily able-bodied administrators and educators will be challenged. Everyone will be informed. This book will be a welcome addition to reading lists in a wide array of academic fields including: Education, Pedagogy, Disability Studies, Human Resources Management, and Sociology."--Provided by publisher.
chapter 1 Almost Passing -- Using Disability Disclosure to Recalibrate Able-Bodied Bias in the Classroom / Julie-Ann Scott Kelly P. Herold -- chapter 2 Teaching on Wheels -- Bringing a Disability Perspective into the Classroom / April B. Coughlin -- chapter 3 How Crip Is Too Crip? -- Reimagining the Presence of Disabled Professors in the Academy / Nadine LeGier Michelle Owen -- chapter 4 My Class, My Disability, My Struggle 1 / Tafadzwa Rugoho Michael S. Jeffress -- chapter 5 Teaching through a Traumatic Brain Injury / Sarah E. Schoper -- section I Teaching with Physical Disability -- chapter 6 (3z(BThe Instructor Is Partially Def(3y (B-- s DHH Professing in Higher Education / Lisa M. Dembouski -- chapter 7 A Dialogue about Disability Praxis between a Deaf Law Professor and a Hearing Education Professor / Michael A. Schwartz Brent C. Elder -- chapter 8 (3z(BIs that Really Our Teacher Professor Person(3y(B? Working from the Boundaries -- s Enabling from Afar / Amin Makkawy -- chapter 9 My Tech Writing Teacher Has Low Vision -- Teachable Moments for Accessibility and Diversity in the Technical Communication Classroom / Gia Alexander -- section II Teaching with Sensory Disability -- chapter 10 To Share or Not to Share? Pedagogical Dilemmas of a Chronically-Ill Lecturer in Teaching with Invisible Disability / Adi Finkelstein -- chapter 11 Negotiations of In/Visible Disability in the Rhetoric Classroom / Rebecca Miner -- chapter 12 Method to Our Madness -- Teaching and Learning Across Mental Disability / Aubry D. Threlkeld Sarah Louise Pieplow -- chapter 13 Teaching (with) Dis/ability and Madness / Mark A. Castrodale -- chapter 14 The Work Around -- How Teaching with Andragogical Practices Can Normalize Learning Disabilities in Education / Kimberly M. Cuny -- chapter 15 Teaching with Augmentative and Alternative Communication / Alyssa Hillary Sam Harvey -- chapter 16 Being Exhibit A -- Teaching AIDS and Music in the University Classroom / Paul Attinello -- section III Teaching with Hidden Disability -- chapter 17 Disclosing Disability around the Water Cooler -- Strategies for Boosting Collegiality in Academe / Pauline T. Newton Michael S. Jeffress Amanda K. Thomas -- chapter 18 The Impact of Having an Instructor with Disability on Student Attitudes toward People with Disabilities / William J. Brown Michael S. Jeffress -- section IV Teaching with Disability -- Engaging Students and Colleagues.
Keywords: Teachers with disabilities